2023
DOI: 10.1111/cid.13204
|View full text |Cite
|
Sign up to set email alerts
|

Modified internal sinus elevation for patients with low residual bone height: A retrospective clinical study

Abstract: Background: We have modified the internal sinus elevation by combining it with the sinus mucoperiosteum stripping procedure, which further increases the indications for the internal lift. Similar long-term clinical follow-up studies and three-dimensional finite element analyses are rare.Objective: This study aimed to investigate the feasibility of the modified internal sinus floor elevation method in patients with low residual bone height using a three-dimensional (3D) finite element model and report on the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We have successfully implemented the procedure in several cases. A retrospective clinical study of this modified procedure was performed, and the results [ 16 ] have been successfully published in the Journal of Clinical Implant Dentistry and Related Research. However, in our subsequent use of the modified internal sinus elevation procedure, we have found that the difference in the angle of the maxillary sinus is an equally important factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have successfully implemented the procedure in several cases. A retrospective clinical study of this modified procedure was performed, and the results [ 16 ] have been successfully published in the Journal of Clinical Implant Dentistry and Related Research. However, in our subsequent use of the modified internal sinus elevation procedure, we have found that the difference in the angle of the maxillary sinus is an equally important factor.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis described above, a three-dimensional (3D) finite element model of the implant, bone and membrane in the maxillary sinus region was established during this experiment to dynamically simulate the separation and lifting of the maxillary sinus floor membrane and study the stress and strain of the maxillary sinus floor membrane when the implant is placed in the maxillary sinus model at different angles of internal sinus elevation. While this study focused on the stresses of the maxillary sinus floor membrane at different sinus angles, some of the 3D model images and experimental data were taken from a previous study by our team [ 16 ]. Rationality was achieved in vivo but not in vitro, utilizing a technique that is not invasive.…”
Section: Introductionmentioning
confidence: 99%